The Impact of Reference Groups on the Purchase Intentions of Sporting Products: The Case for Spectatorship and Participation - Panjarat Pransopon,; Danupol Hoonsopon, (Asian Academy of Management Journal, 2019)
The purpose of this research is to investigate the impact of reference groups and different types of sports consumers on their purchase intentions for sporting products. Several studies have examined the role of reference groups (private and public) on purchase intentions in the sports marketing area. However, there is a shortage of investigation into the impact of reference groups for each type of sports consumer (spectatorship and participation). Additionally, the effect of strangers on the purchase intentions of sports consumers has been overlooked. After drawing from the social identity theory and conducting experimental research with 593 respondents who have interest in either watching or playing sports, as well as analysing the research with structural equation modelling, the results show that private groups influence the purchase intentions of participation for sporting products. However, public groups and strangers influence the spectatorship purchase intentions of sporting products. This study provides a contribution to the social identity theory by revealing that reference groups provide a diverse effect on purchase intentions for each type of sports consumer.